MOTIVATIONAL SKILLS FOR ENHANCING ADULT LEARNERS EFFECTIVE PARTICIPATION IN ADULT LITERACY PROGRAMME - Ugwa, Uzoma .A; Umezulike, Prof. Nneka .A. (Journal of Continuing and Development Education, 2023)
Motivation is the key that drives adults to learn and develop interest in their studies, but most times, cultivating this interest is hard especially when the learners are adult who are engaged in so many activities. It can be really challenging to create genuine interest for some students but using the right motivational skills, will make them enjoy learning. This paper therefore defined the context of motivation and motivational skills. It also looked at some of the motivational styles, techniques and some of the motivational skills that aid effective learning. Also, factors the teacher needs to consider before choosing any motivational skills were also emphasized. Moreso, relevance of motivational skills in relation to adult education were also extensively discussed. Finally, it concluded by encouraging educators to always use motivation to achieve effective learning.